1988
DOI: 10.1530/jrf.0.0820015
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte size and intrafollicular position in polyovular follicles in rabbits

Abstract: Healthy follicles with 2-24 oocytes were observed in adult rabbit ovaries during all phases of folliculogenesis from primary to preovulatory follicles. Most follicles contained 2-3 oocytes which developed according to their topographical situation in the follicle. The central oocyte in a normal topographical situation has an almost normal growth and development up to metaphase II and cumulus expansion. The peripheral oocytes grow more slowly: most do not attain the normal size or resume meiosis and remain surr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

1988
1988
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 9 publications
1
10
0
3
Order By: Relevance
“…Undercounting was reduced to a minimum in our study by inspecting the ovaries for newly ruptured follicles under a stereomicroscope. Polyovular follicular development has been described for rabbits (Adams, 1960;-Mufti et al, 1988). From in-vitro fertilization studies conflicting data have been reported on the fertilization of ova recovered in endometriosis patients.…”
Section: Resultsmentioning
confidence: 99%
“…Undercounting was reduced to a minimum in our study by inspecting the ovaries for newly ruptured follicles under a stereomicroscope. Polyovular follicular development has been described for rabbits (Adams, 1960;-Mufti et al, 1988). From in-vitro fertilization studies conflicting data have been reported on the fertilization of ova recovered in endometriosis patients.…”
Section: Resultsmentioning
confidence: 99%
“…1) et de ré pondre aux gonadotrophines exogè nes (hamster [13]). Cependant, le devenir des follicules polyovocytaires varie selon les auteurs : soit tous les follicules polyovocytaires entrent en atré sie [2], mais les taux d'atré sie sont similaires entre mono-et polyovocytaires (lapin [14] humain [8]). D'autres auteurs considè rent que certains follicules peuvent se dé velopper et ovuler (rat [15], hamster [13]).…”
Section: Caracte´ristiques Morphologiques Et Fonctionnelles Des Folliunclassified
“…Pour connaitre la qualité des diffé rents ovocytes, leur localisation dans le follicule et leur taille semble avoir beaucoup d'importance. En effet, les ovocytes situé s en pé riphé rie sont plus petits, se dé veloppent moins vite et n'atteignent pas la taille maximale (lapin [14]). La diffé rence de taille entre le plus gros ovocyte et le plus petit est en moyenne de 10 à 20 % (porc [12]).…”
Section: Caracte´ristiques Des Ovocytes De Follicules Polyovocytairesunclassified
“…Since then, the polyovular follicles from ART treatment have been reported [10][11][12][13][14][15][16][17][18]. Jones et al [10] and Dandekar et al [11] retrieved more than one oocyte from 8% of the aspirated follicles via laparoscopy in ART treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In animal studies, an oocyte needs to be located at a certain position inside a follicle to reach an appropriate size that allows it to resume meiosis [18]. The position of oocytes inside of a follicle may play an important role in the normal maturation of oocytes.…”
Section: Introductionmentioning
confidence: 99%